Temperature induced degradation of InAlGaN multiple-quantum well UV-B LEDs. Issue 1792 (12th May 2015) - Glaab, Johannes; Ploch, Christian; Kelz, Rico; Stölmacker, Christoph; Lapeyrade, Mickael; Ploch, Neysha Lobo; Rass, Jens; Kolbe, Tim; Einfeldt, Sven; Mehnke, Frank; Kuhn, Christian; Wernicke, Tim; et al.
ABSTRACT: The reliability of InAlGaN multiple quantum well LEDs emitting around 308 nm has been investigated. The UV-B LEDs were stressed at constant current and current density, while the heat sink temperature was varied between 15°C and 80°C. The results reveal two different modes of the decrease of the optical power during aging. First, a fast reduction of the optical power within the first 100 h (mode 1) can be observed, followed by a slower degradation for operation times >100 h (mode 2). Mode 1 can be described as an initial degradation activation process which saturates after a certain time, whereas the second degradation mode can be described by a square-root time dependence of the optical power, suggesting a diffusion process to be involved. Both degradation modes are accompanied by changes of the I-V characteristic, particularly the reverse-bias leakage current and the drive voltage. Furthermore, the degradation behavior is strongly influenced by the temperature. Both, the maximum reduction of the optical power and the increase of the leakage current become stronger at higher temperatures.